INVESTASI ETIS (ETHICAL INVESTMENT) (KONSEP, DASAR PERTIMBANGAN DAN PENDEKATAN) - Abdullah Mubarok (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Ethical investment has experienced very fast and high growth over the last decade. The growth and development of this investment occurs both at the local (Indonesian) level and at the global level. In Indonesia, the growth and development of ethical investment can be seen from the increasing number of ethical-based stock indices and the value of stock market capitalization in each of these indices. Meanwhile at the global level, it can be seen from the increase in the value of ethical investments, especially in the five main world markets, namely Europe, the United States, Japan, Canada and Australia and New Zealand. Underlying this phenomenon needs to be explored further on the issue of ethical investment. This article tries to explore more deeply ethical investing, especially regarding the concepts, basis for decisions and approaches (strategies) in ethical investment activities.